2014
DOI: 10.1021/cm501522v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Magnetic Properties of Rare-Earth Cobalt Arsenides, RCo2As2 (R = La, Ce, Pr, Nd)

Abstract: Four rare-earth cobalt arsenides, RCo 2 As 2 (R = La, Ce, Pr, Nd), were obtained by reactions of constituent elements in molten Bi. The use of Bi flux also allowed the growth of representative single crystals. All compounds are isostructural and belong to the ThCr 2 Si 2 type (space group I4/mmm). The formation of Co vacancies is observed in all structures, while the structures of La-and Ce-containing compounds also show incorporation of minor Bi defects next to the R crystallographic site. Correspondingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 51 publications
12
36
0
Order By: Relevance
“…This assumption is further supported by properties of the later members of R2Co12As7 series. It is also in agreement with our findings of AFM 4f-3d coupling in RCo2P2 and RCo2As2 structures with early lanthanides [25,26,33].…”
Section: R2co12as7 (R = Tb Dy) Both Tb2co12as7 and Dy2co12as7show Vsupporting
confidence: 93%
See 2 more Smart Citations
“…This assumption is further supported by properties of the later members of R2Co12As7 series. It is also in agreement with our findings of AFM 4f-3d coupling in RCo2P2 and RCo2As2 structures with early lanthanides [25,26,33].…”
Section: R2co12as7 (R = Tb Dy) Both Tb2co12as7 and Dy2co12as7show Vsupporting
confidence: 93%
“…Such behavior is characteristic of AFM coupling between the R 4f and Co 3d magnetic moments, suggesting the ferrimagnetic (FiM) ground state for these materials. This finding is also in accord with the FiM behavior reported for Pr2Co12P7 and Nd2Co12P7 [13], as well as for PrCo2As2 and NdCo2As2 [33]. The AFM 4f-3d coupling is well illustrated by the magnetization isotherms recorded for Nd2Co12As7 at different temperatures (Fig.…”
Section: Magnetic Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…This is further evidence that the magnetic moments prefer to align along a-axis. Similar lowered remanent magnetization and larger coercivity when the field is applied perpendicular to the easy axis of magnetization was also observed for Ce 0.95 Bi 0.05 Co 1.85 As 2 [33]. …”
Section: Magnetic Propertiessupporting
confidence: 76%
“…When switching to isostructural arsenides, tin flux failed to produce any RCo 2 As 2 phases. Instead Bi flux was successfully applied (Thompson et al, 2011(Thompson et al, , 2014bTan et al, 2016aTan et al, , 2018. Detailed structural characterizations revealed that Bi is capable of partially replacing R 3+ cations, probably due to its trivalent nature (Thompson et al, 2011).…”
Section: Ba 3 CD 2 As 4 In Pb Fluxmentioning
confidence: 99%